Dimensões comunicacionais no conceito de escultura social de Joseph Beuys: um processo de tradução criativa - Vicini, Magda Salete (2011)
This investigation confront and checks the amplitude of the concept of Social Sculpture based in the authors Tisdall (2008), Kuoni (1993), Bunge (1998) and Borer (2001), and relates to all works produced by Joseph Beuys. Contextualize the concept of social sculpture of Joseph Beuys in relation to his life and his art, from theories and concepts as the Rudolf Steiner s anthroposophy and Romanticism in Hegel, Schiller, Goethe and Novalis. Present some considerations about his work with researchers as Durini (2008), Lauf (1993), Harlan (2005), Bunge (1998), Tisdall (1998, 2008) and Adriani, Konnertz and Tomas (1979). Approach the context of art from visual arts critics who analyze his artwork from the 1960s. The desired yield, say, the intention in this context, is close to an understanding of the inter-semiotic translation Plaza (2008), considering it as symbolic translation. We conceive that the concept of Social Sculpture was close to the critique of current communication, among these, the analysis of democratic representation in the absence of Negri and Hardt (2005), the process of communication and interaction between man and nature in Maturana and Varella (1995 ), the critique of technology Flusser (2008) and the invisible economy of knowledge as Gorz (2005). Since the concept of Social Sculpture was understood, the aim is to make a translation of this concept in digital production, considering aspects of translation theory. To clarify our translation option in the theoretical considerations in support of Benjamin (2008), Gentzler (2008), Steiner (2005) and Campos (1997, 2005 and 2006), building a creative process for the translation that is down from our experience as an artist, teacher, manager of Brazilian culture and citizenship, reading and directing the social and cultural contexts the concept of Social Sculpture. Thus, it was fundamental the understanding of the translation originated in linguistic and language as building elements of human culture - the basis of the human essence in the work of Joseph Beuys -, the authors Rudolf Steiner (2001), Cassirer (2001, 2005), Bachelard (2008), Steiner (2008) and Baudrillard (1993). We got the concluded that the Social Sculpture is presented as critical to communication and culture, and means to provoke thoughts, words and actions. Joseph Beuys sought the meeting with the human essence of the lived reality, using art as a way to challenge and expand the notion of human beings and the the world. From this understanding, made the translation of digital production: Otherspoken/ListenImage